Provenance of the Lower Carboniferous Horton Group, Petit-de-Grat Island, Nova Scotia, as revealed by detrital zircon ages - Force, Eric R.; Barr, Sandra M. (Atlantic Geology, 2013)
A quartz sandstone bed in a dominantly conglomeratic section in the central part of the Lower Carboniferous Horton Group on Petit-de-Grat Island, offshore southern Cape Breton Island, Nova Scotia, contains detrital zircon grains with ages ranging from mid-Devonian to Archean. The similarity of the Devonian and Neoproterozoic age spectrum to ages of igneous units in the adjacent Avalonian Mira terrane, in particular the Coastal belt, indicates that it was the main source area. This interpretation is supported by the similarity of the Neoproterozoic and older detrital zircon age spectrum to that of the detrital zircon age spectrum in a Cambrian sandstone unit from the Mira terrane. This interpretation indicates post-depositional dextral fault motion between the Isle Madame area and the Coastal belt.RésuméUne couche de grès quartzeux repérée dans une section principalement conglomératique dans la partie centrale du groupe de Horton du Carbonifère inférieur sur l’île Petit-de-Grat, au sud de l’île du Cap-Breton, en Nouvelle- Écosse, contient des grains de zircon détritique dont l’âge va du Dévonien moyen à l’Archéen. La similitude du spectre d’âge du Dévonien et du Néoprotérozoïque avec celui des unités ignées trouvées dans le terrane Mira d’Avalon adjacent, en particulier la ceinture côtière, indique qu’il s’agit de la région source principale. Cette interprétation est étayée par la similitude du spectre d’âge du zircon détritique du Néoprotérozoïque et de périodes plus anciennes avec celui du zircon détritique trouvé dans une unité de grès du Cambrien provenant du terrane Mira. Cette interprétation indique un mouvement postsédimentaire d’une faille dextre entre la région de l’île Madame et la ceinture côtière.[Traduit par la redaction]